The never-ending story: discursive legitimation in social media dialogue - Glozer, Sarah Alice; Caruana, Robert; Hibbert, Sally (SAGE, 2018)
This paper explores the dialogical dimensions of discursive legitimation in social media sites to understand how organisations produce knowledge of legitimacy in concert with their stakeholders. Drawing on the dialogical theories of Bakhtin and Nikulin, we consider the potential for conceptualising discursive legitimation as a product of dissent: an on-going ‘allosensual’ dialogue comprised of different voices and competing knowledge claims. We explore this through a micro-level analysis of organisation-led social media sites, wherein organisational practices are increasingly subjected to public scrutiny and where knowledge of legitimacy can be significantly shaped. Our dialogical lens highlights three inter-related functions of discursive legitimation. Discursive authorisation represents attempts to assume a credible ‘voice’ in-relation-to-‘other’ voices, within the dialogue. Discursive validation represents attempts to subject truth claims about legitimacy to rational, normative and moral verification. Finally, discursive finalisation represents attempts to harmonise dissent, either by co-opting or antagonising stakeholders towards consensus. Primarily, this paper unpacks the role of social media in legitimation processes, whilst also elaborating on organisational attempts to control stakeholder dialogue in online contexts.